Simplify:
$(i)$. $(-4)^3$
$(ii)$. $(-3)\times(-2)^3$
$(iii)$. $(-3)^2\times(-5)^2$
$(iv)$. $(-2)^3\times(-10)^3$

AcademicMathematicsNCERTClass 7

Given:
$(i)$. $(-4)^3$

$(ii)$. $(-3)\times(-2)^3$

$(iii)$. $(-3)^2\times(-5)^2$

$(iv)$. $(-2)^3\times(-10)^3$


To do: To simplify the given terms.

Solution:

$(i)$. $(-4)^3$

$=-4\times-4\times-4$

$=-64$

$(ii)$. $(-3)\times(-2)^3$

$=(-3)\times(-2)\times(-2)\times(-2)$

$=24$

$(iii)$. $(-3)^2\times(-5)^2$

$=(-3)\times(-3)\times(-5)\times(-5)$

$=225$

$(iv)$. $(-2)^3\times(-10)^3$

$=(-2)\times(-2)\times(-2)\times(-10)\times(-10)\times(-10)$

$=8000$
raja
Updated on 10-Oct-2022 13:38:51

Advertisements